Determination and Comparison of the Amino Acid Composition of Seventeen Lagenaria siceraria Varieties and One Variety of Citrullus colocynthis Seed Flours - Sabo, Haoua; Sadou, Hassimi; Amoukou, Ibrahim Adamou; Alma, Mousbahou Malam; Sidikou, Ramatou Seini; Saadou, Mahamane; Suleman, Bilbis Lawal (Pakistan Journal of Nutrition, 2015)
Seeds from 17 varieties of Laganaria siceraria and 1 variety of Citrullus colocynthis were analyzed for their proximate amino acids composition. These seeds were produced on the Abdou Moumouni University, Faculty of Sciences and Technology, experimental field. The seeds showed significant difference in their protein content: Lagenaria siceraria (29.45 g/100 g), Citrullus colocynthis (12.40 g/100 g) but were closely related in their amino acids profile. Glutamic, aspartic acids and arginine were the most abundant amino acids while Total Sulphur Amino Acids (TSAA = methionine + cystine) were the limiting amino acids. Leucine was the most concentrated essential amino acid. The percentages of essential amino acids of the seeds were also closely related: Lagenaria siceraria (42.85%) and Citrullus colocynthis (41.51%). Despite a similar amino acids profile, the chemical concentrations of each amino acid were significantly different between varieties (p<0.001) exception of leucine (p = 0.06), showing that the varieties have some genetic differences. In L. siceraria seeds, TSAA ranged from 3.26% to 4.35% and Total Aromatic Amino Acids (TAAA) ranged from 27.14 to 30.55%. In C. colocynthis seeds the concentrations were 4.5 and 27.99%, respectively. When comparing the amino acids in these varieties with the recommended FAO/WHO provisional pattern, the seeds were adequate in histidine, TAAA, threonine and TSAA but supplementation was required for lysine in all varieties and for isoleucine, leucine and valine in some varieties. Predicted Protein Efficiency Ratios (PER) was 1.98 in C. colocynthis and ranged from 1.81 to 2.33 in L. siceraria.